Echoes of Silence: Postcolonial Feminist Voices in Hosseini’s And The Mountains Echoed - Chaker Abas (European Scientific Journal, ESJ, 2025)
This paper examines the silenced yet resonant voices of Afghan women in Khaled Hosseini’s And the Mountains Echoed (2013) through the lens of postcolonial feminist theory. Methodologically, the study employs a qualitative textual analysis, conducting a close reading of the novel’s multi-generational narrative. The analysis is systematically guided by a theoretical framework of C. T. Mohanty, G. C. Spivak, and D. Kandiyoti to interrogate how gendered silence is inscribed, resisted, and reimagined within the novel’s multinational and multigenerational frameworks. Drawing on their works, the study explores the interplay between patriarchal structures, cultural memory, and geopolitical displacement. It argues that Hosseini’s portrayal of female characters somehow creates a textured tapestry of various levels of resistance - from silent endurance to rebellious action, and deferred agency, thereby challenging dominant monolithic representations of Afghan womanhood. This study contributes a nuanced framework for reading Afghan female subjectivity as a site of both reassurance and agency. It offers a postcolonial feminist methodology for analysing literary representations that resist reductive victimhood and accentuate complex, situated forms of resistance.